A Randomized Controlled Trial of Multiple Versions of an Acceptance and Commitment Therapy Matrix App for Well-Being. Issue 2 (March 2019) - Krafft, Jennifer; Potts, Sarah; Schoendorff, Benjamin; Levin, Michael E.
Mobile apps may be useful in teaching psychological skills in a high-frequency, low-intensity intervention. The acceptance and commitment therapy (ACT) matrix is a visual tool to help develop psychological flexibility by categorizing moment-to-moment experience and is well suited to a mobile app. This pilot study tested the effects of a simple and complex version of a novel app using the ACT matrix in two distinct samples: help-seeking individuals ( n = 35) and students receiving SONA credit ( n = 63). Findings indicated no differences between app conditions and a waitlist condition in the SONA credit sample. However, in the help-seeking sample, improvements were found on well-being and valued action in participants who used the app, with greater improvements and app adoption for those using a complex version with additional skills. A mobile app based on the ACT matrix has benefits for help-seeking individuals, but supplementary features may be necessary to support consistent use and benefits.